Benzoin condensation: a kinetic monitoring at the oil-water interface - Singh, Anshu; Kumar, Anil (ChemistrySelect, 2018)
The overall kinetics of condensation of benzaldehyde to benzoin has been discussed here with an aim to develop a better understanding of the change in reactivity of the interfacial reaction in the presence of co-solvents. A key aspect of the 'on water' reaction is the chemistry between solvent and reactants that occur at the oil-water interface. In particular the orientation of water molecules at the interface plays a key role in catalyzing the reaction. An initial increase in the rate constants of reaction is observed, followed by sharp fall in the reaction kinetics. An interesting interplay of hydrophobicity, hydrogen bonding and polarity of the binary mixture is inevitable in the present study. The observations are nevertheless important reference point for future investigations of 'on water' reactions.

Binary mixtures of aprotic and protic ionic liquids demonstrate synergistic polarity effect: an unusual observation - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2020)
In this communication, we demonstrate the solute-solvent and solvent-solvent interactions in the binary mixtures of two aprotic ionic liquids, namely 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, with the protic ionic liquid 1-methylimidazolium acetate. The synergistic effects as expressed by the solvatochromic parameter are noted. This observation is in contrast to the mixing of protic ionic liquids 1-methylpyrrolidium acetate and 4-methylmorpholine acetate with 1-methylimidazolium acetate, respectively. It appears that the synergistic effects in the binary mixtures of aprotic and protic ionic liquids are caused by the formation of hydrogen bonds, since cations are dominant H-bond donors while anions are dominant H-bond acceptors. Preferential solvation models are used to describe the solute-solvent interactions in the binary ionic liquid mixtures.
Keywords: binary mixture; Ionic liquid; polarity; Preferential solvation; synergetic effect